Dental auxiliaries' knowledge, attitude, and practices regarding noma prevention: A cross-sectional study in Northwestern Nigeria - Mujtaba Bala; Muhammad Abubakar Kaura; Anas Bawa Tsafe; Rufai Jaafar; Sadeeq Abubakar Fawa; Ahmad Abdulkadir (Wolters Kluwer Medknow Publications, 2024)
Objective: The objective is to evaluate dental auxiliaries' knowledge, attitudes, and practices for the prevention of noma disease. Materials and Methods: This was a cross-sectional study conducted over 6 months. After obtaining ethical clearance from the Sokoto and Zamfara State Ministries of Health, all consenting dental assistant staff who met the selection criteria were administered a validated questionnaire containing 17 questions assessing the respondents' knowledge, attitudes, and practices. They were recruited using a self-administered questionnaire. The overall score was classified as "low" if the average score was 50% or less (50% or less), satisfactory (51%-69%), or good (70% or more). Data were analyzed using IBM SPSS version 20 software. Results: A total of 149 respondents returned the questionnaire, of which 80 (53.7%) were men and 69 (46.3%) were women. The mean ± standard deviation age of respondents was 27.37 ± 7.00 years, with a range of 20-58 years. The age of respondents was divided into four groups, and the majority of 112 respondents (75.2%) were in their 30s. The majority of respondents, 141 (94.6%), know about the prevention of noma disease. The total respondent score was 1827 points (72.1%), which was evaluated as "good." Conclusion: Knowledge, attitudes, and practices of dental auxiliaries in the field of noma prevention are good. Dental auxiliaries, if supervised and appropriately trained, can play a role in noma prevention by actively participating in and disseminating information on specific preventive measures such as scaling and polishing.